2015
DOI: 10.4172/2155-9872.1000245
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Method for the Quantitation of Polysorbate 20 and 80 to Study the Compatibility between Polysorbates and m-Cresol in the Peptide Formulation

Abstract: A highly sensitive method has been developed for the quantitation of polysorbate 20 (PS20) and 80 (PS80) in therapeutic peptide formulations. A mixed-mode HPLC column was used to separate polysorbates from the peptide and other excipients, and a charged aerosol detector (CAD) was used for the detection. The method was capable of reporting polysorbates as low as 5 ppm, and the sensitivity could be further improved on a needed basis. The method has been used to study the compatibility between polysorbates and m-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Furthermore, PS20 and PS80 were spiked to the peptide formulation at 20 ppm PS20 (0.002%) and 50 ppm PS80 (0.005%). In conclusion, Shi et al (2015) confirmed that higher levels of polysorbate 20 and 80 (50 ppm, 100 ppm, 800 ppm) are incompatible with m-cresol leading to increased turbidity of the solution and loss of polysorbate content due to PS degradation. In comparison, PS80 was less compatible with m-cresol than PS20.…”
Section: Interactions Of Preservatives With Excipientssupporting
confidence: 63%
See 2 more Smart Citations
“…Furthermore, PS20 and PS80 were spiked to the peptide formulation at 20 ppm PS20 (0.002%) and 50 ppm PS80 (0.005%). In conclusion, Shi et al (2015) confirmed that higher levels of polysorbate 20 and 80 (50 ppm, 100 ppm, 800 ppm) are incompatible with m-cresol leading to increased turbidity of the solution and loss of polysorbate content due to PS degradation. In comparison, PS80 was less compatible with m-cresol than PS20.…”
Section: Interactions Of Preservatives With Excipientssupporting
confidence: 63%
“…Even though these incompatibility issues are known, many protein formulations including preservatives and polysorbates do exist on the market. Recently, studies were conducted focusing on interactions between preservatives and polysorbates [112,113]. These studies differed from earlier study as they did not analyze the impact of polysorbates on the antimicrobial activity of preservatives but focused on the impact of preservatives on the stability of polysorbates [114].…”
Section: Interactions Of Preservatives With Excipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with a mass spectrometer could be considered. Today, only a few studies have hypothesized that homologues of the same type have a different response, but none have offered proof or explanations [46,50]. In order to deepen the explanation of this phenomenon, molecular modeling could be considered to understand how molecules are organized together during the formation of particles.…”
Section: Alcohol Ethoxylated Response Factor In Hilic-cadmentioning
confidence: 99%
“…In their work, Shi et al highlighted that the correlation between peak area and polysorbate concentration were not the same between two similar molecules polysorbate 20 and polysorbate 80 4 [46]. They explained this difference by the length of fatty acid chains present in PS80, which are longer than in PS20, and induced higher responses on HPLC-CAD.…”
mentioning
confidence: 99%